Income Tax “Need to Knows” for Military Families - Barbara O'Neill; Martie Gillen; Kristen Jowers (EDIS)
This publication discusses general information about income tax terminology, general information about income tax rules, rates, and refunds, military-specific income tax challenges, military-specific income tax regulations, five income tax planning tips for military families, and income tax resources. Written by Barbara O’Neill, Martie Gillen, and Kristen Jowers, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2024.